Transcriptomic meta-analysis identifies dysregulated pathways and potential therapeutic targets in Vestibular Schwannoma - Ebrar Altınalan; Aleksandra Panina; Robert Fredriksson; Ayse Arzu Şakul; Helgi B. Schiöth (PLoS ONE, 2026)
Vestibular schwannoma (VS) is a benign Schwann cell–derived tumor that frequently causes progressive hearing loss and vestibulocochlear dysfunction, substantially impacting quality of life. The molecular mechanisms underlying VS pathobiology remain poorly defined, and reliable biomarkers or targeted therapies are lacking. This study aimed to delineate the molecular landscape of VS through a transcriptome-wide meta-analysis. We performed a genome-wide random-effects meta-analysis of four independent Affymetrix microarray datasets from the Gene Expression Omnibus (GEO) database. Differential expression analyses were conducted with and without covariate adjustment. Gene Ontology enrichment and DrugBank-based drug–gene interaction analyses were subsequently applied to characterize biological pathways and assess translational potential. Across the meta-analysis, more than 3,200 differentially expressed genes were identified in the covariate-free model. After applying a more stringent threshold (|metaLFC| > 1 and FDR < 0.05), 1,095 genes remained differentially expressed, with high concordance between the covariate-free and covariate-adjusted models. Downregulated genes included extracellular matrix and stromal components ( MFAP5 , FABP4 , DCN ), and sensory- and synapse-related transcripts ( SLC22A3 , LGI1 ). Upregulated genes included immune- and inflammation-associated genes ( TREM2 , CCL3 , CCL4 , L1CAM ) and proliferative regulators ( CCND1 , RAB31 , MOXD1 ). Functional enrichment highlighted extracellular matrix remodeling, immune modulation, sensory signaling, and cell cycle pathways. Notably, many of the most strongly dysregulated genes have not previously been associated with VS. Drug–gene interaction analysis identified multiple dysregulated genes with known pharmacological targets, suggesting potential translational relevance. This transcriptome-wide meta-analysis provides a comprehensive overview of gene expression patterns in VS, highlighting alterations related to extracellular matrix organization, sensory and synaptic processes, immune-associated signaling, and cell cycle–related pathways. The study highlights novel disease-associated genes and pathways and may help prioritize candidates for further investigation, including those with potential relevance for therapeutic targeting.